2016
DOI: 10.1159/000444192
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Risk Factors for Cervical Spine Injury from Pediatric Trauma Registry

Abstract: Background: Cervical spine injuries are rare in children. Our goal is to establish guidelines for cervical spine clearance that are practical for our pediatric population, and, in the process, to reduce the risk of radiation exposure from unnecessary advanced imaging. Methods: We retrospectively reviewed the records from the registries of two pediatric trauma centers from the past 11 years (January 2002 to June 2013). Patients aged 1 month to 17 years, who had a CT scan of the cervical spine due to trauma indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
2
7
0
1
Order By: Relevance
“…17 Ugalde et al, 18 found a male dominance, every 2 in 3 patients, in those with cervical injury after blunt trauma. Chaudhry et al, 19 also revealed similar results, in which CSI patients were more likely to be male.…”
Section: ) Sexmentioning
confidence: 60%
See 1 more Smart Citation
“…17 Ugalde et al, 18 found a male dominance, every 2 in 3 patients, in those with cervical injury after blunt trauma. Chaudhry et al, 19 also revealed similar results, in which CSI patients were more likely to be male.…”
Section: ) Sexmentioning
confidence: 60%
“…Risk factors for cervical spine injury in children Year-olds were more likely to able sustain an upper cervical spine injury than adults 8-12-Year-olds were at higher risk for atlanto-occipital injury.SexUgalde et al18 2018 66% of males with the cervical spinal injury in the pediatric cohort Chaudhry et al19 2016 Patients with cervical spine injuries were more likely to be male (p-value 0.02)…”
mentioning
confidence: 99%
“…23,24 Three additional protocols supplemented NEXUS with an additional novel clearance element. 15,16,19,26 To elaborate, the protocol in Sun et al 16 and McMahon et al, 15 whose studies utilized the same algorithm, added appropriate communication to NEXUS criteria; the protocol in Moore et al 19 added normal range of motion; and, the protocol in Chaudhry et al 26 added PEDSPINE criteria 2 (Supplemental Table 2A, Supplemental Digital Content 3, http://links.lww.com/SLA/D855). All 3 of these protocols were applied to the entire cohort with no lower limit of age.…”
Section: Triage Criteriamentioning
confidence: 99%
“…Grundvoraussetzung für die Diagnosestellung ist eine umfassende körperliche Untersuchung des Kindes. Die Inspektion auf Verletzungszeichen, Verformungen und das Abtasten (Druck und Klopfschmerz, Stufen, Versetzungen, tastbare Lücken zwischen Dornfortsätzen, Hämatome, Kontusionen, Muskelhartspann) des gesamten Rückens vervollständigen die Basisuntersuchung [3]. Ist die Palpation der gesamten Wirbelsäule schmerzfrei, kann die Prüfung der Beweglichkeit folgen.…”
Section: Klinische Untersuchungunclassified